2020
DOI: 10.1093/eurheartj/suaa045
|View full text |Cite
|
Sign up to set email alerts
|

May Measurement Month 2018: an analysis of blood pressure screening results from Sudan

Abstract: To raise awareness of high blood pressure (BP) levels and associated risk factors among the Sudanese population. A cross-sectional study was conducted in six Sudanese states during the period May–August 2018. The study area included public indoor and outdoor areas, institutes, and service facilities. A questionnaire for collecting the data was employed including demographic data, along with three consecutive BP measurements. Data were collected by trained volunteers. Hypertension (HTN) was defined as a systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Some previous research [ 21 ] showed an association between no diabetes with undiagnosed HTN, which we found in unadjusted analysis with undiagnosed HTN versus diagnosed HTN. Policy implications are that increased public awareness campaigns, and screening of HTN are needed to reduce undiagnosed HTN in Sudan [ 10 , 31 ]. Health systems through primary healthcare need to be strengthened and universal health coverage to prevent and manage NCDs, including hypertension [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous research [ 21 ] showed an association between no diabetes with undiagnosed HTN, which we found in unadjusted analysis with undiagnosed HTN versus diagnosed HTN. Policy implications are that increased public awareness campaigns, and screening of HTN are needed to reduce undiagnosed HTN in Sudan [ 10 , 31 ]. Health systems through primary healthcare need to be strengthened and universal health coverage to prevent and manage NCDs, including hypertension [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronically, HTN is implicated in atherosclerosis by damaging the blood vessel walls and possibility of plaque deposition. Alternatively, the high prevalence of HTN in general population in different regions including Sudan [34,35], which is by far overweighing the ACS prevalence, gives false impression that HTN is the predominant IDH risk factor. Although, the above variables are well established risk factors for ACS [36], in the present study the frequency of these factors, except smoking, were not significantly different between the clinical types of ACS, the UA, NSTEMI and STEMI (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sudan stepwise survey 2016 showed that, the national prevalence of raised blood pressure (RBP) was 31.5%. The serious findings was among participants with RBP who are not currently on medication where the highest reported from Darfur (93.2%) and Kordofan (92.0%) regions, while the lowest was reported from Khartoum region (76.5%) (6) Within NHIF context, chronic diseases represent about 18% of the total annual visits. Hypertension and diabetes are the main types of diseases which represent around 40% for each (7) .…”
Section: Chronic Diseasesmentioning
confidence: 96%